2019
DOI: 10.11604/pamj.2019.33.40.17953
|View full text |Cite
|
Sign up to set email alerts
|

Triplane fracture of the proximal tibia: a case report and literature review

Abstract: Triplane fractures of the proximal tibia are less well known than the distal extremity. The diagnosis is based on a good analysis of X-rays and possibly CT images to better plan the management. The authors reports a triplane fracture of the proximal tibial in a 12 year old boy treated by closed reduction and internal fixation. To our knowledge, only a dozen cases have been reported in the literature with generally a good evolution of the fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Lateral DISCUSSION: Proximal tibia fractures in most cases, are high energy injuries, resulting in skeletal injuries, ligament injuries, and multisystem dysfunction. Without proper intervention and management, these injuries will lead to poor outcomes like instability, loss of motion, posttraumatic arthritis, wound breakdown, and infection 7 . Open reduction and internal fixation for this type of complex intra-articular fractures have high chances for soft tissue complications like infection and skin necrosis 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Lateral DISCUSSION: Proximal tibia fractures in most cases, are high energy injuries, resulting in skeletal injuries, ligament injuries, and multisystem dysfunction. Without proper intervention and management, these injuries will lead to poor outcomes like instability, loss of motion, posttraumatic arthritis, wound breakdown, and infection 7 . Open reduction and internal fixation for this type of complex intra-articular fractures have high chances for soft tissue complications like infection and skin necrosis 8 .…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that both management approaches are effective. (16,17) To perform dual column plating, two distinct incisions are required, which means there is a significant possibility of soft tissue injury and periosteal injury. (18) Thirty-five patients were taken for this study, having a mean age of 38.54±12.65 years; male patients had a higher frequency than female patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that triplane fractures of the proximal tibia are relatively rare because of the symmetrical closure pattern of the physis in contrast to the asymmetrical closure of the distal tibial physis. 2 , 4 , 5 It has also been suggested that the medial and lateral collateral ligaments of the knee pass over the epiphysis and insert onto the tibial metaphysis, which protects the epiphysis from fractures by allowing stress to bypass the epiphysis, being transmitted directly to the metaphysis. 5 …”
Section: Discussionmentioning
confidence: 99%
“… 2 , 4 , 5 It has also been suggested that the medial and lateral collateral ligaments of the knee pass over the epiphysis and insert onto the tibial metaphysis, which protects the epiphysis from fractures by allowing stress to bypass the epiphysis, being transmitted directly to the metaphysis. 5 …”
Section: Discussionmentioning
confidence: 99%